1988
DOI: 10.2466/pr0.1988.63.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Locus of Control, and Achievement of High School Seniors

Abstract: High school seniors in the top and bottom quartiles of achievement ( ns = 30) showed locus of control was strongly related to tension-stress, those internally oriented showing lower tension-stress. Number of life changes was associated with tension-stress; girls scored higher than boys. School-related stress was deemed to be an important factor in the lives of these students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…In our own studies, we have found girls to be more stressed than boys both as high school freshmen (Thomas, Shoffner, and Groer, 1988) and as seniors (Gro~r, Thomas, and Shoffner, in press). Similar findings have been reported by Cole and Sapp (1988). Adolescent girls also report more health problems than do boys (cf.…”
Section: Ability To Manage Angersupporting
confidence: 78%
“…In our own studies, we have found girls to be more stressed than boys both as high school freshmen (Thomas, Shoffner, and Groer, 1988) and as seniors (Gro~r, Thomas, and Shoffner, in press). Similar findings have been reported by Cole and Sapp (1988). Adolescent girls also report more health problems than do boys (cf.…”
Section: Ability To Manage Angersupporting
confidence: 78%
“…These include the influence of maternal behavior on affective reactions, which can differ for male and female offspring (Burnham & Harris, 1992;Reid, 1994). Sex difference in anxiety and in coping strategies may also underlie the present findings (Cole & Sapp, 1988;Mak, Blewitt, & Heaven, 2004). Women tend to have higher levels of anxiety sensitivity than men (Peterson & Reiss, 1992;Stewart, Conrod, Gignac, & Pihl, 1998).…”
Section: Discussionmentioning
confidence: 80%
“…The mean norm-weighted stress scores of females were higher regardless of geographic location; urban females reported highest stress levels. Other researchers using life change event scales have reported similar findings (Burke & Weir, 1978;Cole & Sapp, 1988;Dise-Lewis, 1988). Reasons for these findings remain unclear.…”
mentioning
confidence: 73%